APLIKASI UNIT PENGOLAH AIR DENGAN TEKNOLOGI MEMBRAN DI UKM ELEKTROPLATING. - Luqman Buchori; Faleh Setia Budi; Heru Susanto (Universitas Wahid Hasyim, 2010)
Electroplating industry is characterized in the metal plating process. This process occurs in the electroplating bath that contains a chemical solution. Before the coating process, the metal material to be coated should be washed first to remove the impurity attached. The metal materials that have been completely coated are then took from the bath and rinsed with water to clean the chemical solution attached at those materials. UD Citra Utama obtaines the water used for cleaning from the well in industry area around the company. Unfortunatley, the water well used is characterized by its relatively high salt content and turbid. Initial water analysis showed that those parameters are beyond the standard of water quality used for cleaning in electroplating industry. The use of this water has negative impact such as decreasing thw water quality, slows down the speed of coating process and eventually decreases the capacity and company income. To solve this problem, we have developed water treatment unit that treats the well water into pure water. The unit contains reverse osmosis (RO) membrane, pump, catridge prefilter and media filter. In addition, the unit is equipped with the accessories such as pressure gauge, flow meter and feed/product tank. The results of evaluation showed that water treatment unit can increase the product capacity 30% from 30 m2 to 39 m2 that correspond to income from Rp. 2000000,- to Rp 2600000,-. In addition, this unit can decrease the company omset from 5% to 0.5%. The water produced from this unit could meet the government role (Peraturan Menteri Kesehatan RI Nomor : 416/MENKES/IX/1990). Keywords : electroplating; water treatment unit; pure water